Influence of historical use of antibiotics toward antibiotic resistance - Fawandi Fuad Alkindi; Rika Yulia; Fauna Herawati; Abdul Kadir Jaelani (Universitas Muhammadiyah Malang, 2019)
A WHO’s Global Surveillance of Antibiotic Resistance showed there is an increase of antimicrobial resistance in Asia between 2013 until 2014. Many studies showed that there is a correlation between prior antibiotic use with antimicrobial resistance case. The primary objective of this study is to analyze the relationship between prior antibiotic use with antimicrobial resistance. İt was a retrospective and descriptive study conducted at Bangil Regional General Hospital. The data collected from the medical record and microbiological test from the patient at the internal ward. Chi-square analysis used for the statistic. This study showed that prior antibiotic use increased 0,399 bigger for antimicrobial resistance rate (p=0,001).